Perinatal Survival and Predictors of Mortality among Mothers with Hypertensive Disorders of Pregnancy at Antenatal care Clinics in Gamo Zone Public Hospitals - Sifer, Samuel Dessu (Ethiop J Health Sci, 2020)
BACKGROUND: Pregnancy induced hypertension represents a significant public health problem throughout the world, which may complicate 0.5%–10% of all pregnancies. It is the leading cause of maternal as well perinatal mortality and morbidity worldwide. Pregnancy induced hypertension is a multisystem disorder unique to pregnancy and results in high perinatal mortality. The objective of this study was to determine the survival status, incidence and predictors of perinatal mortality among mothers with pregnancy induced hypertension at antenatal clinics of Gamo Zone public hospitals. METHODS: Facility-based retrospective cohort study was conducted among selected 576(192 exposed and 384 unexposed) antenatal care attendants' record at Gamo Zone public hospitals from 1(st) January 2018 to 31(st) December 2018. Data were entered into Epi data version 3.02 and exported to SPSS V 25 for analysis. Kaplan Meier survival curve together with log rank test was fitted to test the survival time. Statistical significance was declared at P-value ≤0.05 using cox proportional hazard model. RESULT: The incidence of perinatal mortality was 124/1000 births. The cumulative proportion of surviving at the end of 4(th), 8(th), 12(th) and 16(th) weeks of follow-up among the exposed groups was 96.9%, 93.5%, 82.1% and 61.6% respectively whereas it was 99.5%, 98.9% and 98.5% at the end of 4(th), 8(th) and 12(th) weeks of follow-up for the non-exposed groups respectively. Parity of ≥5(AHR: 6.3; 95%CI: 1.36,10.55), mothers who delivered at <34 weeks of gestation(AHR:7.8; 95%CI: 2.6,23.1), being preterm(AHR:6; 95%CI: 5.3,19.2), perinatal birth weight ≤2500gm(AHR:6.1; 95&CI: 1.01,37.9), vaginal deliveryn(AHR:2.7; 95%CI:1.13,6.84), maternal highest systolic blood pressure level ≥160mmHg (AHR: 2.3; 95%CI: 1.02,5.55) and prepartum onset of pregnancy induced hypertension (AHR: 6; 95%CI: 5.3,19.2) were statistically significant in multivariable analysis. CONCLUSION: The risk of perinatal mortality was high among the mothers with pregnancy induced hypertension compared to those of pregnancy induced hypertension free mother,s and the perinatal mortality rate was high. High parity, low gestational age, low number of antenatal care visits, low birth weight, vaginal delivery, antepartum onset of pregnancy induced hypertension and highest maternal systolic blood pressure level were the independent predictors of perinatal mortality.